Misperceptions and misapplications of research in family law cases: Myths of "Parental Alienation Syndrome" and implanted false memories. Issue 1 (2nd January 2019) - Shaw, Morgan
Abstract: This introduction highlights the need for a special issue in the Journal of Child Custody on the misconceptions and misapplications of research within the family law arena. First, an examination of why these topic areas are relevant is conducted including an overview of the types of false assumptions and biases that are still very much present within the family legal system and child custody evaluations, and how they have an ongoing negative impact on the lives of children and families. Then, this introduction introduces and outlines the different ways that the articles included in this first of the double special issue address the misconceptions contributing to faulty practice, including false memories, and provide a critical examination of the different ways that parental alienation is assessed and treated. Both issues within this two-part special issue present articles that clearly identify better and more appropriate directions for future research in order to strengthen child custody evaluations and the family law system as a whole.